PENGARUH DUE PROFESSIONAL CARE, TIME BUDGET PRESSURE, KOMPETENSI, MOTIVASI, DAN INDEPENDENSI TERHADAP KUALITAS AUDIT (Survei pada Kantor Akuntan Publik di Kota Surakarta dan Yogyakarta) - Wulandari Wulandari; Dewi Saptantinah Puji Astuti; Fadjar Harimurti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
The purpose of this research is to analyze the significance of the influence of due professional care, time budget pressure, the auditor competence, motivation and independence of the Auditors of the quality audit in the public accountant of the city of Surakarta and Yogyakarta. This study used a survey method, the type of data the data used was qualitative and quantitative data, the source data used the primary data and secondary data. The population in this study are all Auditors working in public accounting in the region of Surakarta and Yogyakarta. The number of samples in the study based on the number of questionnaires returned, i.e. as many as 47 respondents. Sampling techniques using acidental sampling. Methods of data collection were used: questionnaire and documentation. Technique of data analysis used the test of validity, reliability test, test the assumptions of classical, and multiple linear regression analysis and test of the absolute difference. The research results obtained conclusions that due professional care, competence, motivation and independence of Auditors Auditors significant positive effect on quality of audit in the public accountant of the city of Surakarta and Yogyakarta, while time budget significant negative pressure effect on quality of audit in the public accountant of the city of Surakarta and Yogyakarta.